Technical Accuracy and Efficiency of Magnetic Resonance Imaging in Evaluation of Uterine Masses in Comparison with Ultrasound - Hind Moafak Abd-Aljabbar; Haider Qasim Hamood; Hussein Hasan Nsaif (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aim of the Study: comparing accuracy, sensitivity and specificity of the magnetic resonance imaging and ultrasound in differentiating and characterizing of uterine masses.Patients and Method: A prospectively studied has been conducted on 41 female patients with suspected uterine masses. They were subjected to ultrasound and magnetic resonance imaging (MRI) examination. Comparison has been performed between modalities to detect and characterize all masses. Statistical parameters that include the specificity, sensitivity, accuracy and positive and negative predictive value have been estimated for the two modalities in all of the uterine masses.Results: Among 41 female patients, majority were diagnosed as leiomyoma 28 (68%), cervical cancer 1 (2%), adenomyosis 7 (17%), endometrial polyp 2 (5%), endometrial carcinoma 2 (5%) and normal 1 patient (2%). Totally 3 (i.e. 7%) patients have been found malignant while 37 (i.e. 93%) have been found benign. For detection of myometrial mass (leiomyoma), the sensitivity between the ultrasound and MRI is 100%, accuracy was (ultrasound: 92% and MRI: 100%). In the classification of myometrial mass (i.e. leiomyoma) site, sensitivity between the ultrasound and MRI has been 21% and 92% respectively and specificity was (ultrasound: 0 and MRI: 100%). All intramural and subserosal lesions are seen in MRI. For picking up degeneration within the leiomyoma MRI are more useful. There have been considerable differences in the diagnosis of the adenomyosis by the MRI in comparison with ultrasound with sensitivity was (MRI: 100% and ultrasound: 71%), and specificity for both was 100%, whereas accuracy was 75% for ultrasound and 100% for MRI. In the detection of the endometrial carcinoma, the MRI has achieved 100% sensitivity and 50% specificity whereas ultrasound had zero sensitivity and specificity was 50%. Among two cases of endometrial polyp, one patient is diagnosed correctly by ultrasound & MRI, the sensitivity for both was 50% and accuracy was (ultrasound: 50% and MRI: 75%). MRI and ultrasound was correctly diagnosis of one patient with cervical cancer with sensitivity and accuracy 100%.